Evaluation of resistance in new hybrid maize genotypes to Northern leaf blight (Exserohilum turcicum) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hidayatullah T, Suliansyah I, Swasti E, Putri NE, Mejaya IMJ. 2025. Evaluation of resistance in new hybrid maize genotypes to Northern leaf blight (Exserohilum turcicum). Biodiversitas 26: 4967-4975. Northern Leaf Blight Disease (NLB), caused by Exserohilum turcicum, is a major foliar disease threatening maize (Zea mays) production in Indonesia. This study aimed to evaluate the resistance of 20 new hybrid maize genotypes developed by Universitas Andalas, along with two control varieties, against NLB. Field trials were conducted in West Sumatra using a randomized complete block design to assess disease resistance and agronomic traits. Multivariate analysis was used to assess 20 new hybrid maize genotypes. The collected data were examined across nine parameters: Plant Height (H), Ear Height (EH), Stem Diameter (SD), Dehusked Ear Weight (DEW), Harvest Moisture (HM), Grain Weight per Ear (GWE), 1000-grain Weight (W1000), Yield Potential (YP), and Northern Leaf Blight (NLB). Results showed that most of the hybrids demonstrated Resistance (R) to Moderate Resistance (MR), with genotypes G4-13, G15-16, G18, and G21 exhibiting high levels of resistance and stability. NLB severity showed significant correlations with all parameters except harvest moisture. Principal component analysis identified three components with eigenvalues greater than one, collectively explaining 86.53% of the total variance. The first two components alone accounted for 74.19% of the variance, highlighting their dominant role in discriminating among genotypes. Cluster analysis produced four clusters, such as cluster 1: G7, G12, G3, G14, and G17; Cluster 2: G10, G19, G2, G20; Cluster 3: G21, G6, G22; and the last, Cluster 4: G15, G8, G16, G9, G13, G18, G4, and G5. The findings indicate that G6 is suitable candidates for advancement to preliminary yield trials, combining superior yield potential with notable resistance to NLB. These outcomes provide practical guidance for breeding programs seeking to produce resilient and productive maize hybrids across variable agroclimatic settings.